New guidelines from the Thrombosis and Haemostasis Society of Australia and New Zealand for the diagnosis and management of venous thromboembolism. Issue 5 (10th February 2019) - Tran, Huyen A; Gibbs, Harry; Merriman, Eileen; Curnow, Jennifer L; Young, Laura; Bennett, Ashwini; Tan, Chee Wee; Chunilal, Sanjeev D; Ward, Chris M; Baker, Ross; Nandurkar, Harshal
Abstract: Introduction: Venous thromboembolism (VTE), including deep vein thrombosis (DVT) and pulmonary embolism (PE), is the third most common cardiovascular disease and, globally, more than an estimated 10 million people have it yearly. It is a chronic and recurrent disease. The symptoms of VTE are non‐specific and the diagnosis should actively be sought once considered. The mainstay of VTE treatment is anticoagulation, with few patients requiring additional intervention. A working group of experts in the area recently completed an evidence‐based guideline for the diagnosis and management of DVT and PE on behalf of the Thrombosis and Haemostasis Society of Australia and New Zealand (www.thanz.org.au/resources/thanz-guidelines ). Main recommendations: The diagnosis of VTE should be established with imaging; it may be excluded by the use of clinical prediction rules combined with D‐dimer testing. Proximal DVT or PE caused by a major surgery or trauma that is no longer present should be treated with anticoagulant therapy for 3 months. Proximal DVT or PE that is unprovoked or associated with a transient risk factor (non‐surgical) should be treated with anticoagulant therapy for 3–6 months. Proximal DVT or PE that is recurrent (two or more) and provoked by active cancer or antiphospholipid syndrome should receive extended anticoagulation. Distal DVT caused by a major provoking factor that is no longer present should be treated with anticoagulant therapy for 6 weeks. For patients continuing with extended anticoagulant therapy, either therapeutic or low dose direct oral anticoagulants can be prescribed and is preferred over warfarin in the absence of contraindications. Routine thrombophilia testing is not indicated. Thrombolysis or a suitable alternative is indicated for massive (haemodynamically unstable) PE. Changes in management as a result of the guideline: Most patients with acute VTE should be treated with a factor Xa inhibitor and be assessed for extended anticoagulation.